2015
DOI: 10.5858/arpa.2015-0196-ra
|View full text |Cite
|
Sign up to set email alerts
|

MiT Family Translocation-Associated Renal Cell Carcinoma: A Contemporary Update With Emphasis on Morphologic, Immunophenotypic, and Molecular Mimics

Abstract: Translocation-associated renal cell carcinoma (t-RCC) is a relatively uncommon subtype of renal cell carcinoma characterized by recurrent gene rearrangements involving the TFE3 or TFEB loci. TFE3 and TFEB are members of the microphthalmia transcription factor (MiT) family, which regulates differentiation in melanocytes and osteoclasts, and MiT family gene fusions activate unique molecular programs that can be detected immunohistochemically. Although the overall clinical behavior of t-RCC is variable, emerging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
84
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 71 publications
0
84
0
2
Order By: Relevance
“…In addition, differentiating between CCRCC and t-RCC may be essential for clinical trial enrollment of patients with advanced disease. 21,22 Translocation RCC is associated with recurrent gene fusions involving transcription factor binding to IGHM enhancer 3 (TFE3; located on band Xp11) or transcription factor EB (TFEB; located on band 6p21), which are both members of the MiT family of transcription factors. [23][24][25] These tumors were formerly classified as Xp11 translocation carcinoma; however, the name has been changed in the 2016 WHO classification to reflect the possibility of non-TFE3 fusion partners in the MiT family (ie, TFEB).…”
Section: Rcc With Clear Cytoplasmmentioning
confidence: 99%
“…In addition, differentiating between CCRCC and t-RCC may be essential for clinical trial enrollment of patients with advanced disease. 21,22 Translocation RCC is associated with recurrent gene fusions involving transcription factor binding to IGHM enhancer 3 (TFE3; located on band Xp11) or transcription factor EB (TFEB; located on band 6p21), which are both members of the MiT family of transcription factors. [23][24][25] These tumors were formerly classified as Xp11 translocation carcinoma; however, the name has been changed in the 2016 WHO classification to reflect the possibility of non-TFE3 fusion partners in the MiT family (ie, TFEB).…”
Section: Rcc With Clear Cytoplasmmentioning
confidence: 99%
“…A study by Stahlschmidt et al 43 demonstrated evidence of a (9,22) translocation, but the tumor did not respond to imatinib. In nine tumors analyzed by Swartz et al, 36 only one case had any aneuploidy.…”
Section: Geneticsmentioning
confidence: 98%
“…Regardless of subtype, both members of the MiT family respond similarly to treatment, although distinctions between subtypes may be more important in the future as more targeted therapies are developed. 22 …”
Section: Classificationmentioning
confidence: 99%
“…Поскольку точка разрыва находится в промоторе, опухоли гиперэкспрессируют нативный TFEB; для выявления этой перестройки также приме-няют FISH-или иммуногистохимический метод. Хотя в большинстве случаев при дифференциальной диаг-ностике MiT-РП главными маркерами выступают TFE3 или TFEB, для уточнения диагноза можно ис-пользовать СА9, панцитокератины, эпителиальный мембранный антиген, а также протеазу катепсин К и меланоцитарные факторы НМВ-45 и Melan-A, экс-прессию которых стимулируют члены семейства MiT [6,12]. В MiT-опухолях зачастую гиперэкспрессиру-ется МЕТ, что указывает на возможность использова-ния ингибиторов МЕТ как противоопухолевых аген-тов.…”
unclassified
“…Примечательно, что биаллельная инак-тивация FLCN в опухоли приводит к активации сиг-нального пути АКТ-mTOR, как и при других типах НСРП. Генетическая лабораторная диагностика при BHDS заключается в анализе мутаций FLCN (секвени-рование экзонов [4][5][6][7][8][9][10][11][12][13][14]. Герминальные мутации FLCN относятся, преимущественно, к типу "loss of function": инсерции, делеции и дупликации со сдвигом рамки считывания, комплексные мутации, нонсенс-мута-ции, мутации сайтов сплайсинга; миссенс-мутации были идентифицированы лишь в единичных случаях.…”
unclassified